O conceito de amor agostiniano a partir de Hannah Arendt - Sanches, Elissa Gabriela Fernandes (2018)
Hannah Arendt developed a doctoral thesis in which she worked on the concept of love in Augustine outside its theological dimension, making Philosophy the interpretative key for her analysis. As a result, the German philosopher focused on the Augustinian contradictions regarding the triad of love: love of God, love of self and, especially, neighborly love, the central issue of her research. As her tools, she used Heidegger's Phenomenology and Philosophy of Existence to reach the core of her problem: how can we love each other and ourselves through the love of God? In our dissertation, we study Hannah Arendt's interpretative analysis in order to highlight another way of understanding the neighborly love (dilectio proximi) of Augustine’s philosophy, seeking to understand if it is at all possible to develop a relationship of charitable love within the space of communal life (vita socialis). Love, for the bishop of Hippo, is the ethical principle that binds human beings, thus forming communities. What Arendt questions is the capacity of love to act, on its own, in this social dimension. Her research will culminate in the discovery that love does not promote any social connections, but that there is something behind it, something primeval that generates this connection from the individual’s birth. This original connection refers to the theological questions of Augustinian thought, namely the equality between human beings originated both in Adam and in Christ, as well as the Christian belief that all individuals are regarded as sinners and in need of grace. It is those parameters that will define, according to Arendt, the bond between individuals - constituting life in society (vita socialis) - and will allow the execution of the Christian commandment, which orders one to love one's neighbor as oneself. In the end, we present the philosophical and theological implications of this Arendtian interpretation space.